Abraham Joshua Heschel dan Filsafat Yahudi Kontemporer - Iqbal Hasanuddin (ILMU USHULUDDIN, 2017)
This paper tries to analize Abaraham Joshua Heschel’s contribution to the Contempprary Jewish Philosophy. In his philosophical works, Heschel tries to formulate the philosophical foundations on the scope and nature of human existence. At this point, the Jewish identities are not only recognized but also integrated as a basic principle: child of agreement. It is about the special relation between the Jewish People and Yahwe in the mode of relation between the Thou (heteronomy, transcendence) and the I (autonomy, immanency). So, as Jewish philosophy, Heschel thought is an effort to make explicit the nature of all Jewish human beings: the agreement with Yahweh. Here, Heschel philosophy has characteristics which belong to All Jewish philosophy in general: defending theological motives to solve the philosophical problems. At this context, Heschel gives the scope and deepness of the Jewish theology and philosophy. Heschel philosophy is full of insights that make the Jewish doctrines very real. Heschel thought can make the modern people aware about the highest problems. Here Heschel has tried to make the bridge between the Jewish philosophy and the modern world view.